Changing approaches to public expenditure management in low-income aid dependent countries - Adrian Fozzard; Mick Foster (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
The present paper critically examines how aid dependent low-income countries have approached the process of public expenditure management reform during the 1990s. It begins with an overview of broader public sector reform initiatives in LDCs which provide the backdrop against which expenditure management reform has taken place. It then assesses progress in six key areas of reform: the role and structure of the State; attempts to improve agency performance; the introduction of resource and expenditure planning tools; measures to improve the governance of public expenditure; the development of new aid management instruments; and finally, recent experiences in improving the poverty reduction impact of public expenditure. It concludes with an assessment of the likely success of these initiatives and the priorities for future interventions.
Keywords: O23; H50; 330; public expenditure management; aid management; public sector reform; Öffentliche Ausgaben; Öffentliche Finanzplanung; Entwicklungshilfe; Low-Income Countries